Preclinical Ultrasound Imaging—A Review of Techniques and Imaging Applications - Moran, Carmel M.; Thomson, Adrian J. W. (Frontiers in Physics, 2020)
Ultrasound imaging is a well-established clinical imaging technique providing real-time, quantitative anatomical and physiological information in humans. The lack of ionising radiation and relative low purchase and maintenance costs results in it being one of the most frequently used clinical imaging techniques with increasing use for guiding interventional clinical procedures. Until 20 years ago, translation of clinical ultrasound practices to preclinical applications proved a significant technological challenge due to the smaller size (25g vs 70kg) and rapid conscious heart-rate (500-700bpm vs 60bpm) of the mouse requiring an increase in both spatial and temporal resolution of 10-20 fold in order to achieve diagnostic information comparable to that achieved clinically. Since 2000 (Foster et al 2000), these technological challenges have been overcome and commercial high frequency ultrasound scanners have enabled longitudinal studies of disease progression in small animal models to be undertaken. Adult, neonatal and embryonic rats, mice and zebrafish can now be scanned with resolutions down to 30 microns and with sufficient temporal resolution to enable cardiac abnormalities in all these species to be identified. In mice and rats, quantification of blood flow in cardiac chambers, renal, liver and uterine vessels and intra-mural tissue movements can be measured using the Doppler technique. Ultrasonic contrast microbubbles used routinely for clinical applications are now being further developed to include targeting mechanisms and drug-loading capabilities and the results in animal models bode well for translation for targeted drug delivery in humans.